Concepções e percepções de uma professora de matemática e de seus alunos do 6º ano do ensino fundamental sobre indisciplina - Lima, Julian da Silva (2015)
The following research tried to investigate the conceptions and the perceptions of the indiscipline in the Math classes of a 6th grade group of an elementary school, located in the town of Marau/ RS. The main question that guided the investigation was: what are the conceptions and the perceptions of a Math teacher and of her 6th grade students of an elementary school about the indiscipline in the classroom? The study was carried out as an approach of qualitative investigation, case study type, using questionnaires and interviews performed with the teacher and her pupils, besides the documents provided by the school. It was anchored, mainly, in the contributions of the Cultural-historical Theory, of Math Didactic and in some authors that deal specifically with the school indiscipline, especially Aquino (1996), Estrela (2002) and Vasconcellos (2010). Through analyses of the content, described in Bardin (2011), it was found that, although the conceptions and perceptions of the students in relation to the indiscipline in the classroom are similar to the teacher´s, they still commit indiscipline acts. In relation to the passive indiscipline, the lack of interest of the students, perceived by the teacher, is summarized to what the students consider as study activity. With regards to the active indiscipline, the reflection in classroom of the meanings appropriated by the students in the social context where they live in was verified. The conclusion is that any rule that is established in classroom must contemplate its pedagogical function so that it is not confused with the blind obedience to the silence imposition. The activities in the classroom can be determinant for a passive posture of the students, being characterized as indiscipline. Finally, in the social interactions to which the students are exposed, they can adopt the values which will trigger postures considered passive indiscipline